Proceedings of SAARC Seminar on Climate Variability in the South Asian Region and its Impacts, Dhaka, Bangladesh, 10-12 December 2002 - SAARC Seminar on Climate Variability in the South Asian Region and its Impacts (2002 : Dhaka, Bangladesh); Quadir, Dewan Abdul; Prasad, Kanti; Hussain, Md. Amirul; SAARC Meteorological Research Centre (Dhaka : SAARC Meteorological Research Centre, 2003)
Papers presented at the seminar.
At head of title: South Asian Association for Regional Cooperation (SAARC).
Icludes statistical tables.
Includes bibliographical references.
Keywords: Climatic changes -- South Asia -- Congresses; Climatic changes -- Environmental aspects -- Congresses